Roy Adaptation Model-Based Nursing Approach for the Individual with Emotional Eating Behavior: Example of Care Plan - Mahire Olcay Çam; Elif Deniz Kaçmaz (Galenos Publishing House, 2022)
This review was made to explain the nursing approach based on the Roy compliance model for the individual with adaptive eating behavior. The Roy Adaptation Model aims to provide holistic care by evaluating the individual in the physiological domain, self-concept domain, role function domain, and interdependence. Emotional eating behavior, which occurs as a response to the emotion felt in a certain life situation, affects the individual in bio-psycho-social areas and may cause maladaptive behaviors. In this article, the Roy Adaptation Model is exemplified in the care of an individual with emotional eating behavior.